Bioinspired Radical‐Mediated Transition‐Metal‐Free Synthesis of N‐Heterocycles under Visible Light - Bains, A.K.; Ankit, Y.; Adhikari, D. (Wiley‐VCH GmbH, 2020)
A redox‐active iminoquinone motif connected with π‐delocalized pyrene core has been reported that can perform efficient two‐electron oxidation of a class of substrates. The design of the molecule was inspired by the organic redox cofactor topaquinone (TPQ), which executes amine oxidation in the enzyme, copper amine oxidase. Easy oxidation of both primary and secondary alcohols happened in the presence of catalytic KOtBu, which could reduce the ligand backbone to its iminosemiquinonate form under photoinduced conditions. Moreover, this easy oxidation of alcohols under aerobic condition could be elegantly extended to multi‐component, one‐pot coupling for the synthesis of quinoline and pyrimidine. This organocatalytic approach is very mild (70 °C, 8 h) compared to a multitude of transition‐metal catalysts that have been used to prepare these heterocycles. A detailed mechanistic study proves the intermediacy of the iminosemiquinonate‐type radical and a critical hydrogen atom transfer step to be involved in the dehydrogenation reaction.
Keywords: Biomimetic catalysis; Hydrogen atom transfer; Pyrimidine; Quinoline